Family and School Counseling - Budi Darmawan; Aulia Morischa; Ira Farah Dina Aisyah; Gusman Lesmana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Family and school counseling play an important role in addressing the complex problems and challenges faced by children and young people. This article explains the benefits and challenges of family and school counseling, the various counseling methods used, and their effectiveness in treating mental health and behavioral problems. With a mixed methods approach, data is collected from parents, teachers, and students to identify the problems and concerns most commonly addressed through counseling, the effectiveness of counseling in addressing those problems, and the factors that contribute to the success of counseling interventions. These findings highlight the importance of early intervention and collaboration between families, schools, and mental health professionals in promoting positive mental health outcomes for children and adolescents.